CHARACTERISTICS OF CIRCADIAN BLOOD PRESSURE PROFILE IN PATIENTS WITH ACUTE CORONARY SYNDROME AND THEIR ASSOCIATION WITH THYROID FUNCTION - Nataliia Kuz; Tetiana Solomenchuk (Acta Medica Leopoliensia)
The paper presents the results of a study of circadian arterial blood pressure (ABP) profile in patients with Acute Coronary Syndrome (ACS) and their association with thyroid-stimulating hormone (TSH) levels.